# 33 p 303 17 now to test for this condition note that

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = S (jβ )P (j (� − β ))dβ 2ω −� �� 2 1 = ω [α (� − 2 − β ) + α (� + 2 − β )]dβ 2ω −� 1 + β 2 � � �� 1 1 = + recalling that g (t)α (t − t0 )dt = g (to ) 1 + (� − 2)2 1 + (� + 2)2 −� Let’s double check our answer, using the analysis equation, and considering that the cosine function can b e expressed as a sum of complex exponentials. 13 X (j� ) = = = = = = = � � � x(t) e −j� dt = −� 0 � � −� � e−|t| cos 2t e−j� dt � e−t cos 2t e−j� dt e cos 2t e dt + 0 −� � � � � �0 �� 1 −j 2t −j� 1 −j 2t −j� t 1 j 2t −t 1 j 2t e e+e e e dt + e dt e+e 2 2 2 2 −� 0 � � 1 0 t(1+j 2−j�) 1 � t(−1+j 2−j�) t(1−j 2−j� ) e +e dt + e + et(−1−j 2−j�) dt 2 −� 20 � � � � 1 1 −1 1 1 −1 + + + 2 1 + j2 − j� 1 − j2 − j� 2 −1 + j 2 − j � −1 − j 2 − j � � � 1 1 1 1 1 + + + 2 1 + j (2 − � ) 1 − j (2 − � ) 1 − j (2 + � ) 1 + j (2 + � ) 1 1 + , which is t...
View Full Document

## This document was uploaded on 02/09/2014.

Ask a homework question - tutors are online